MAJOR INORGANIC IONS IN BULK PRECIPITATION FROM COASTAL URBAN AND MONTANE ATLANTIC FOREST SITES IN SOUTHEASTERN BRAZIL - Patricia A. de Souza; William Z. de Mello (Química Nova, 2024)
Bulk precipitation (BP) samples were collected at two coastal urban sites and two montane Atlantic Forest (400 and 1000 m altitude) areas in southeastern Brazil from August 2008 to August 2009. These samples were analyzed for the major inorganic ions (H+, Na+, K+, Ca2+, Mg2+, Cl- and SO42-) found in rainwater. The concentrations of inorganic nitrogen species (NH4+, NO3- and NO2-) were compiled from a previous study. The volume-weighted mean (VWM) concentrations of inorganic ions differed spatially, with higher values at the coastal urban and coastal periurban sites. On a molar basis, Cl- and Na+ together comprised 60% of the total inorganic constituents at the coastal urban site and 34-42% at the other three sites, as it is the closest to the ocean. Magnesium was also primarily associated with sea-salt aerosol. Non-sea-salt (nss) fractions of K+, Ca2+ and SO42- comprised 68-93% of their VWM concentrations, indicating the contribution of natural (mostly biogenic) and anthropogenic (SO2 oxidation for the latter) sources. Finally, we found that the acidity of BP at the four sampling sites is primarily controlled by the NH4+, nss-Ca2+, nss-SO42-, and NO3- ions, resulting in VWM pH values ranging from 5.60 (lower montane forest) to 5.98 (coastal periurban site).